Day 3 - 1130 - Levac.pdf - Gill, Philip (Cranfield University, 2023)
The granulometric composition of NC Mario Paquet and Ian Levac. GD Canada 9th International Nitrocellulose Symposium Presentations
Keywords: 'nitrocellulose'